If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 10a + 4b + 3a + -25b = 0 Reorder the terms: 10a + 3a + 4b + -25b = 0 Combine like terms: 10a + 3a = 13a 13a + 4b + -25b = 0 Combine like terms: 4b + -25b = -21b 13a + -21b = 0 Solving 13a + -21b = 0 Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '21b' to each side of the equation. 13a + -21b + 21b = 0 + 21b Combine like terms: -21b + 21b = 0 13a + 0 = 0 + 21b 13a = 0 + 21b Remove the zero: 13a = 21b Divide each side by '13'. a = 1.615384615b Simplifying a = 1.615384615b
| -7/3X=-3 | | 7j+3-4j+9=0 | | 9a+6b=-45 | | 4.5-4(1-7z)=15.5 | | h^3+2=40 | | 12.29+.09x=13.04+12x | | 2.5dicks+1=3dicks-4 | | 6xy-6y-1=0 | | 4(1-6f)=23 | | h^3+2h^2-40=0 | | 5x-4+2x=180 | | (A+5)+(a-3)= | | 16+X=25-X | | 3(x+2)-2(x-4)=28 | | 4(-0.5)+2y=-1 | | 2+7x-38=29 | | x=2x^2-4x+20 | | 42+8*2= | | 3s+8s-3= | | 10x-5=2x-10 | | 5-(b/6)=3 | | (9x^2)-x=0 | | 5x^3/2-8=0 | | d/5=3/10 | | -s+3=5s+11 | | 5c-5=625 | | -28.5=4+6(b-5) | | (-3z^4)(2)^5/-9z^3 | | 15a-7a-8a= | | 7-5x=19-(6x+7) | | 3x(4x-5)(3x-4)= | | 21.50+2x=50 |